(untitled) (Research, Society and Development, 2021)
Aims: A systematic review to determine the effect of physical activity and religiosity on anxiety, depression, stress and quality of life in older people. Methods: The LILACS, MEDLINE/PUBMED, SCIELO, and COCHRANE databases were searched. Titles, abstracts and keywords of original articles published in English from January 1990 to January 2019 were examined using the following DeCS descriptors: anxiety, depression, stress, quality of life, active, sedentary, religiosity, ageing, aging, older people. The operator ‘or’ was used between the descriptors ageing, aging and older people. In the screening, exclusion criteria were applied. Eighteen studies, from the initial sample of 47,494, remained at the end of this process. Results: This systematic review found that most of these eighteen studies focus on depression (16), stress (12), anxiety (11) and QOL (11). Depression was the foremost ageing concern. Conclusions: Although these descriptors are so often studied today, their synchronized relationship has not yet been studied. Further studies should be conducted to assess the effect of physical activity and religiosity on depression, anxiety, stress and quality of life in older people.